Implementasi Standard Operating Procedure (SOP) Penyelenggaraan Metting di Hotel Bintang Empat Padang : Sebuah Studi Kualitatif - Patricia Novira; Hendri Azwar (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Abstract. The writing of this thesis aims to find out the implementation of the Standard Operating Procedure (SOP) for Organizing Meetings in Padang Four Star Hotels. The approach used in this research is descriptive qualitative. Observation, interviews, and documentation are used for the data collection process. There are 4 respondents from banquet employees, and 3 respondents from guests who have used meeting services at Hotel Bintang Empat Padang. By listening and transcribing and using NVivo software to analyze the data. The results of the research obtained that the implementation of the Standard Operating Procedure (SOP) for Organizing Meetings at the Four Star Hotel Padang has not been optimal. seen from the role of event technicians (engineering), officers, supervisors, and banquet managers who have not fully implemented properly according to the Standard Operating Procedure (SOP) that has been set. Companies can consider conducting training and periodic evaluation and supervision to ensure that all banquet employees have adequate knowledge of the Standard Operating Procedure (SOP). Keywords: , ,